The students difficulties in learning speaking using TikTok Aplication (Case study at the tenth grade students of MA Raudlatul Ulum Klampis) - Sifak, Nurus; Kiptiyah, Mariyatul (English Teaching Journal : A Journal of English Literature, Language and Education, 2024)
The purpose of this article is to identify and analyze the difficulties students face in learning to speak using TikTok social media, In addition, this research also aims to understand the barriers that arise, as well as to explore potential solutions that can help students overcome these challenges and maximize the benefits of learning through TikTok. This research method uses qualitative with a case study approach. Qualitative research with a case study approach provides several advantages in understanding phenomena in depth and contextually. The researcher provides a more in-depth picture of the phenomenon of student difficulties under study. Based on the results of the interviews, there are several similar answers including, Most students have difficulty understanding and using the features in the TikTok application. In addition, limited internet quota or Wi-Fi access is an obstacle for some students. On the other hand, there are also technical problems, there are student cell phones that cannot be used to open TikTok. Many students also felt less confident in creating and uploading videos on TikTok social media.